Marketing Strategy and the Optimal Production Schedule - Leitch, Robert Alan (Management Science, 1974)
Incorporation of marketing strategy in production planning can reduce overall costs and significantly increase profits. In this paper a solution procedure similar to the traditional Holt, Modigliani, Muth, and Simon production smoothing model is used to find a combined marketing and production plan in which advertising promotion is utilised to avoid peak-load production costs by shifting seasonal demand for a product. The solution procedure is applicable to a wide variety of market characterizations, and the technique may also be readily adapted to analyse impacts of various aspects of market behavior on the optimal production schedule.